Educational management and school coexistence in educational institutions in Peru - Magallanes Almeyda, Flor De María (2024)
School coexistence constitutes a fundamental element in the comprehensive training of students. This is why the Ministry of Education (MINEDU) alludes to the need to build harmonious and balanced human relationships between all members of the educational community as a shared responsibility. Unfortunately, cases of violence within educational institutions are frequent and increasingly numerous, having reached alarming figures, including physical, psychological and sexual violence, perpetrated by students, teachers and administrative staff. The eradication of school violence as a fundamental factor in school coexistence has to do with the rights to freedom, the free development of personality, and not to be subjected to mistreatment and torture, all of which are constitutionally protected. However, we cannot lose sight of the fact that the problem of the impact on school coexistence is derived from the structural violence generated by the State itself due to the neglect of the needs of the population, which generates tensions and serious social conflicts that exacerbate spirits inclining them towards destructive attitudes. In this article, a panoramic review is made of the way in which school coexistence develops in Peruvian educational institutions and the factors that affect it.